2021
DOI: 10.1002/ejic.202100646
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Reaction Between Co(II) Complexes and Peroxymonosulfate

Abstract: Advanced oxidation technologies often use peroxymonosulfate in the presence of Co II aq . It is commonly assumed that the reaction of Co(H 2 O) 6 2 + with HSO 5 À yields Co III aq and SO 4 *À . DFT results point out that first Co II (SO 5 )(H 2 O) 2 is formed. The homolysis of Co II (SO 5 )(H 2 O) 2 to yield (H 2 O)Co II (SO 5 )OH * + SO 4 * À , is exothermic but has a large activation energy. However the cobalt is not oxidized in this reaction. Co II (SO 5 )(H 2 O) 2 reacts with a second HSO 5 À to form Co II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Hydroxocobalamin hydrochloride (Sigma, St. Louis, MO, USA; HOCbl; ≥96%), Oxone (Sigma; 2KHSO 5 · K 2 SO 4 · KHSO 4 ), terephthalic acid (TA; Sigma-Aldrich, St. Louis, MO, USA; 98%), 2-hydroxyterephthalic acid (J&K), Orange II sodium salt (Sigma-Aldrich; ≥85%) were used without additional purification. The content of KHSO 5 in OXONE was determined by the reported procedure [ 7 ]. Concentrations of Cbl stock solutions were determined using UV-visible spectroscopy via conversion of Cbl to its dicyano-form (extinction coefficient is 30,400 M −1 ∙cm −1 at 368 nm [ 47 ]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxocobalamin hydrochloride (Sigma, St. Louis, MO, USA; HOCbl; ≥96%), Oxone (Sigma; 2KHSO 5 · K 2 SO 4 · KHSO 4 ), terephthalic acid (TA; Sigma-Aldrich, St. Louis, MO, USA; 98%), 2-hydroxyterephthalic acid (J&K), Orange II sodium salt (Sigma-Aldrich; ≥85%) were used without additional purification. The content of KHSO 5 in OXONE was determined by the reported procedure [ 7 ]. Concentrations of Cbl stock solutions were determined using UV-visible spectroscopy via conversion of Cbl to its dicyano-form (extinction coefficient is 30,400 M −1 ∙cm −1 at 368 nm [ 47 ]).…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested that cobalt species act as a Fenton reagent in the reaction with HSO 5 − [ 6 ]. However, the most recent explanation of the mechanism of Co(II)-assisted HSO 5 − activation includes the consequent binding of two SO 5 2− molecules which results in O-O bond labilization in one of SO 5 2− ligands, and the liberation of sulfate radicals [ 7 ]. Another study demonstrates the pronounced oxidizing properties of the Co(II)-SO 5 2− complex as a primary intermediate in the Co(II)/peroxymonosulfate system [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of HSO 5 − with Co(H 2 O) 6 2+ and with Co II (P 2 O 7 )(H 2 O) 2 2− require more than one peroxymonosulfate to form radicals [ 46 ].…”
Section: Other Fenton-like Reactionsmentioning
confidence: 99%
“…invoked a hypothetical aqueous Co­(II)–OOSO 3 – complex to explain this observation. The density functional theory-based calculations also proposed the formation of Co­(II)–OOSO 3 – complex intermediates during the activation of PMS by aqueous Co­(II) . However, both of the aqueous Co­(IV)-oxo and Co­(II)–OOSO 3 – complexes have been rarely experimentally captured or spectroscopically characterized in the literature.…”
Section: Introductionmentioning
confidence: 99%